The Effect of Ethnic Self-Identity on the Kadazandusun Sense of Community - Getrude C. Ah Gang @ Grace (2018)
The aim of this study is to examine the effect of the ethnic self-identity of the Kadazandusun people on their sense of community and its four constituent elements. This study involved 242 Kadazandusun participants. A set of questionnaires consisting of three sections was used to measure research variables. Section A measured the demographic profile (age, gender, ethnicity, location, and education level); Section B made use of the Ethnic Self-Identity Scale, consisting of 14 items that measure the two components of ethnic self-identity (i.e., ethnic affirmation, & ethnic denial); and Section C measured the sense of community (i.e., reinforcement of needs, membership, influence & shared emotional connection). The study revealed that ethnic affirmation contributed to a sense of community and its four elements. Ethnic confirmation showed a significant contribution of 23% to the sense of community (β=.48, t(212)=7.93, p =.00). Ethnic confirmation contributed 18% to the reinforcement of needs (β=.43, t(212)=7.19,p=.00); it contributed 19% to variance in membership (β=.44, t(212)=7.50, p=.00), 18% to variance in influence (β=.43, t(212)=7.15, p=.00); and 19% to variance in shared emotions (β=.43, t(212)=7.30, p=.00). Ethnic denial did not show a significant influence on the sense of community. The findings showed that Kadazandusuns who are high in ethnic affirmation (that is, they identify themselves with their group) engage in community activities, are proud of their cultural heritage, and have good interactions with in-group members, characteristics which help to form a strong sense of community.